(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Perforated gastroduodenal ulcer remains one of the most common surgical emergencies and is associated with substantial postoperative morbidity and mortality. Conventional management based on wide laparotomy and forced radical operations is accompanied by a high incidence of purulent-septic and wound complications and prolonged rehabilitation. The expanding role of laparoscopic and video-assisted techniques requires objective evidence comparing their early results with those of traditional open surgery.